2023
DOI: 10.3390/horticulturae9080860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Aminolevulinic Acid (5-ALA) on Physicochemical Characteristics and Growth of Pomegranate (Punica granatum L.)

Abstract: The pomegranate is one of the most essential crop fruits in the world. 5-Aminolevulinic acid (ALA) regulates the growth and development of 5-year-old pomegranate. However, for plenty of pome crops, conventional information on the physio-chemical characteristics underlying 5-ALA is limited. Therefore, in this study, we applied four different concentrations of 5-ALA treatments (0 mg L−1, 10 mg L−1, 20 mg L−1, 50 mg L−1, and 100 mg L−1), where 0 mg L−1 was considered as a control group, to evaluate the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…After a series of experiments in five provinces with different ecological environments, ALA has been officially authorized as a new plant growth regulator for apple coloration [251]. Then, similar effects of ALA were reported in peaches [252], pears [253,254], grapes [255][256][257][258], litchi [259,260], pomegranates [261], and mangoes [262]. In addition to fruit coloration, soaking wheat seeds with 50 mg L −1 ALA not only improves frost tolerance but also increases anthocyanin accumulation in coleoptiles [263].…”
Section: Promoting Fruit Coloration and Flavonoid Biosynthesismentioning
confidence: 91%
“…After a series of experiments in five provinces with different ecological environments, ALA has been officially authorized as a new plant growth regulator for apple coloration [251]. Then, similar effects of ALA were reported in peaches [252], pears [253,254], grapes [255][256][257][258], litchi [259,260], pomegranates [261], and mangoes [262]. In addition to fruit coloration, soaking wheat seeds with 50 mg L −1 ALA not only improves frost tolerance but also increases anthocyanin accumulation in coleoptiles [263].…”
Section: Promoting Fruit Coloration and Flavonoid Biosynthesismentioning
confidence: 91%
“…5-aminolevulinic acid (5-ALA) is the key precursor in the biosynthesis of all porphyrin compounds [8]. It promotes chlorophyll synthesis and facilitates photosynthesis [9]. It has been shown that foliar spraying of 5-ALA inhibits the harmful effects of different types of crop stress [10,11].…”
Section: Introductionmentioning
confidence: 99%